Inorganic and black carbon aerosols in the Los Angeles Basin during CalNex. Issue 4 (19th February 2013) - Ensberg, J. J.; Craven, J. S.; Metcalf, A. R.; Allan, J. D.; Angevine, W. M.; Bahreini, R.; Brioude, J.; Cai, C.; Coe, H.; de Gouw, J. A.; Ellis, R. A.; Flynn, J. H.; et al.
Abstract : [1] We evaluate predictions from the Community Multiscale Air Quality (CMAQ version 4.7.1) model against a suite of airborne and ground‐based meteorological measurements, gas‐ and aerosol‐phase inorganic measurements, and black carbon (BC) measurements over Southern California during the CalNex field campaign in May/June 2010. Ground‐based measurements are from the CalNex Pasadena ground site, and airborne measurements took place onboard the Center for Interdisciplinary Remotely‐Piloted Aircraft Studies (CIRPAS) Navy Twin Otter and the NOAA WP‐3D aircraft. BC predictions are in general agreement with observations at the Pasadena ground site and onboard the WP‐3D, but are consistently overpredicted when compared to Twin Otter measurements. Adjustments to predicted inorganic mass concentrations, based on predicted aerosol size distributions and the AMS transmission efficiency, are shown to be significant. Owing to recent shipping emission reductions, the dominant source of sulfate in the L.A. Basin may now be long‐range transport. Sensitivity studies suggest that severely underestimated ammonia emissions, and not the exclusion of crustal species (Ca 2 +, K +, and Mg 2 + ), are the single largest contributor to measurement/model disagreement in the eastern part of the L.A. Basin. Despite overstated NO x emissions, total nitrate concentrations are underpredicted, which suggests a missing source of HNO3 and/or overprediction of deposition rates. Adding gas‐phase NH3 measurements and size‐resolved measurements, up to 10 μ m, of nitrate and various cations (e.g. Na +, Ca 2 +, K + ) to routine monitoring stations in the L.A. Basin would greatly facilitate interpreting day‐to‐day fluctuations in fine and coarse inorganic aerosol. Key points: We measured inorganic gas‐ and aerosol‐phase species during CalNex We compare ground‐based and airborne measurements to CMAQ predictions Measure/model agreement varies depending on the species and location